Expression of the chemokine superfamily in rheumatoid arthritis - HOSAKA, S.; AKAHOSHI, T.; WADA, C.; KONDO, H. (Clinical and experimental immunology, 1994)
SUMMARY The infiltration of leucocytes into the Joint of rheumatoid arthritis (RA) is believed to be mediated by chemotactic factors released by activated cells. In this study, examination was made of the gene expression and production of the chemokine superfamily in RA patients by reverse transcriptase‐polymerase chain reaction (RT‐PCR) and immunoprecipitation. Cultured synovial fibroblasts were found capable of expressing and producing IL‐8, GRO, monocyte chemotactie and activating factor (MCAF), macrophage inflammatory protein‐la (MIP‐1α), MIP‐1β and RANTES in response to IL‐1α, The expression of IL‐8, GRO. MCAF, MIP‐1α, and MIP‐1β was clearly shown to increase in freshly isolated synovial fluid mononuclear cells (SFMC) of RA patients, in contrast to peripheral blood mononuclear cells (PBMC) of RA patients and normal subjects. The gene expression of RANTES appeared to be the same for RA SFMC. RA PBMC, and normal PBMC. Thus, the over‐expression of various chemokines may promote the recruitment of inflammatory cells into rheumatoid inflamed joints.